A new template to study callosal growth shows specific growth in anterior and posterior regions of the corpus callosum in early childhood. (10th April 2015) - Ansado, Jennyfer; Collins, Louis; Fonov, Vladimir; Garon, Mathieu; Alexandrov, Lubomir; Karama, Sherif; Evans, Alan; Beauchamp, Miriam H.; Brain Development Cooperative Group
Abstract Most of the studies conducted on the development of the corpus callosum (CC) have been limited to a relatively simple assessment of callosal area, providing an estimation of the size of the CC in two dimensions rather than its actual measurement. The goal of this study was to revisit callosal development in childhood and adolescence by using a three‐dimensional (3D) magnetic resonance imaging template of the CC that considers the horizontal width of the CC and compares this with the two‐dimensional (2D) callosal area. We mapped callosal growth in a large sample of youths followed longitudinally (N = 370 at T1; N = 304 at T2; and N = 246 at T3). Both techniques were based on a five‐section subdivision of the CC. The results obtained with the 3D method revealed that the rate of CC growth over a 4‐year period in the rostrum, the genu, the anterior body and the splenium was significantly higher in the youngest age group (< 7 years) than in older groups, indicating an intense period of development in early childhood for the anterior and posterior parts of the CC. Similar results were obtained when 2D callosal area was used for the anterior and posterior parts of the CC. However, divergent results were found in the mid‐body and the caudal body of the CC. As shown by differences between 2D estimations and actual 3D measurements of callosal growth, our study highlights the importance of considering the horizontal width in measuring developmental changes in the CC.